1970
DOI: 10.1017/s0022149x00021404
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Irradiation on the Infective Stage Larvae of the Nematode, Oesophagostomum columbianum and their Use as a Vaccine

Abstract: The effect of irradiation on the survival, behaviour and immunogenicity of the infective (3rd stage) larvae of O. columbianum was studied. The findings reported are:1. Irradiation with up to 160,000 r does not significantly alter the survival of the larvae when stored at 4°C and at room temperature (26–32°C) for a period of 42 days.2. Irradiation at 15.000 r to 40,000 r results in progressively fewer adults developing but more nodules being formed in the intestinal wall. Irradiation at 80,000 r results in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1977
1977
1995
1995

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Similar immunological unresponsiveness has been shown in three-month-old lambs against Trichostrongylus colubriformis (see GREGG et al, 1978). Although development of an acquired resistance in animals to nodular worms has been demonstrated (MONNIG, 1934;SARLES, 1944;ROBERTS et al, 1962;DHAR & SINGH, 1968), it has not been found possible to stimulate more than a marginal protective immunity in lambs and kids aged up to three months following immunization with irradiated larvae (DHAR & SINGH, 1970;SHARMA & DHAR, 1979). This led us to speculate whether young animals showed immunological un-responsiveness also to 0. columbianum but our present findings, which show between 64-7 and 71-9% protection in the immunized lambs, suggest that this may not be so.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Similar immunological unresponsiveness has been shown in three-month-old lambs against Trichostrongylus colubriformis (see GREGG et al, 1978). Although development of an acquired resistance in animals to nodular worms has been demonstrated (MONNIG, 1934;SARLES, 1944;ROBERTS et al, 1962;DHAR & SINGH, 1968), it has not been found possible to stimulate more than a marginal protective immunity in lambs and kids aged up to three months following immunization with irradiated larvae (DHAR & SINGH, 1970;SHARMA & DHAR, 1979). This led us to speculate whether young animals showed immunological un-responsiveness also to 0. columbianum but our present findings, which show between 64-7 and 71-9% protection in the immunized lambs, suggest that this may not be so.…”
Section: Discussionmentioning
confidence: 94%
“…The highly significant differences observed in the percentage establishment of nodules between the immunized and control groups, and significantly high percentage of nodules from immunized animals containing histotrophic stages confirm our earlier findings that formation of nodules and arrested development of larvae within them may be one of the manifestations of acquired resistance (DHAR & SINGH, 1968;SHARMA & DHAR, 1979). As acquired resistance to 0. columbianum under natural and experimental conditions is always accompanied by the formation of nodules in the intestinal wall and in extra-intestinal sites (MONNIG, 1934; SARLES, 1944; SHELTON & GRIFFITHS, 1968; DHAR & SINGH, 1970;SHARMA & DHAR, 1979), all vaccines, whether viable or nonviable, that may be used for immunoprophylaxis against 0. columbianum in sheep and other animals are likely to lead to nodule formation. The numbers of nodules may further increase with reinfections occurring in animals in the field.…”
Section: Discussionmentioning
confidence: 99%